2019
DOI: 10.1111/jan.14142
|View full text |Cite
|
Sign up to set email alerts
|

Impact of deep oropharyngeal suctioning on microaspiration, ventilator events, and clinical outcomes: A randomized clinical trial

Abstract: Aims To evaluate a deep oropharyngeal suction intervention (NO‐ASPIRATE) in intubated patients on microaspiration, ventilator‐associated events and clinical outcomes. Design Prospective, two‐group, single‐blind, randomized clinical trial. Methods The study was conducted between 2014 ‐ 2017 in 513 participants enroled within 24 hr of intubation and randomized into NO‐ASPIRATE or usual care groups. Standard oral care was provided to all participants every 4 hr and deep oropharyngeal suctioning was added to the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 48 publications
(105 reference statements)
0
11
0
3
Order By: Relevance
“…In contrast, other researchers used α-amylase to evaluate outcomes of interventions and reported data related to VAE. In these studies, no relationships were observed between α-amylase levels and development of VAE ( 12 , 16 ).…”
Section: Clinical Significancementioning
confidence: 80%
See 4 more Smart Citations
“…In contrast, other researchers used α-amylase to evaluate outcomes of interventions and reported data related to VAE. In these studies, no relationships were observed between α-amylase levels and development of VAE ( 12 , 16 ).…”
Section: Clinical Significancementioning
confidence: 80%
“…Once oral secretions are aspirated, it is unknown how long α-amylase is detectable in pulmonary secretions. Studies with multiple measures detected α-amylase up to 14 days after intubation ( 11 , 12 , 16 ), and no changes in either the α-amylase values or T/O ratio over time ( 16 ). Reported values may reflect ongoing aspiration around the ETT cuff and/or stability of α-amylase in the pulmonary system once aspiration occurs.…”
Section: Application Of Alpha-amylase Resultsmentioning
confidence: 99%
See 3 more Smart Citations